Biomarkers for Assessment of Fracture Healing in Dogs with Tibial Fracture - Mehdi, Ghulam; Bhagavantappa,; Shivaprakash, B; Kumar, Dilip; Venkatgiri, D; Kumar, Vijay; S K, M Shweta (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The study was conducted in 12 clinical cases of dogs presented to the Department of Veterinary Surgery and Radiology in Bidar. They  were randomly divided into two groups consisting of 6 animals each. In group I fracture was repaired using interlocking nail (ILN) and  in group II with locking compression plate. The fracture healing was studied after the operation on day 0 (immediate), 15th, 30th and  60th. In both groups, calcium, phosphorus and alkaline phosphatase levels were estimated pre-operatively and on the above days for  assessment of fracture healing. The mean values of serum calcium and alkaline phosphatase gradually increased from the pre-operative  day reaching significantly the highest (p
Keywords: Alkaline phosphatase; Calcium; Biomarkers,; , Dog,; Fracture healing,; Phosphorus.